Pengaruh Olahraga Gateball dan Motivasi kerja terhadap disiplin pegawai Lingkup PUPR di Mamuju Sulawesi Barat - Mallarangeng, Firman Juang; Aqil, Muhammad; S, Ramli (Pascasarjana Universitas Muhammadiyah Mamuju, 2024)
Gateball is a game and a new sport in West Sulawesi. This sport then developed and became an attractive option in terms of promoting sports and sports in society. In this game there is no age, because it does not require physical and mental strength to play this sport. However, skills are needed that will emerge from daily practice in the field. Along the way, this sport has developed so much in West Sulawesi, it is not difficult to find people playing gateball when we pass along the arterial road of Mamuju. This is a new phenomenon, because people playing in the yard of the office of the National Road Implementation Center of the Ministry of Public Works and Public Housing, West Sulawesi, seem to have become a new community that has never existed before. No less interesting is that those playing in the office yard on the arterial road are people who come from other places, or are not employees of the office that has the gateball field. There is another interesting thing, that it is regularly scheduled, local matches are held regularly every month. Finally, as time went by, several other agencies in the West Sulawesi Provincial Government took part in playing actively every day in the field. Researchers explore the possibility that there is an influence of gateball games on work motivation so that employee discipline increases. The author conducted research at the Department and Center of the Ministry of Public Works and Public Housing in West Sulawesi, as a work area where many employees play gateball on the Mamuju arterial field, the gateball game center as well as the traffic secretariat in West Sulawesi which is the yard of the National Road Implementation Agency. In early 2024 a survey was conducted on 30 respondents. Data is processed and analyzed using simple linear regression and simple linear regression techniques. The research results show that the gateball game has a positive effect on employee discipline, 36%, work motivation has a positive effect on employee discipline, 61.8%. The influence of gateball sports and work motivation together has a positive effect on employee discipline on average by 48.9%.